Dejavniki gibalne aktivnosti in z zdravjem povezane kakovosti življenja - Slabe Erker, Renata (Obzornik zdravstvene nege, 2014)
Introduction: Physical activity can be beneficial to physical and mental health. The following article aims to identify factors influencing physical activity and possible measures to enhance these activities. The purpose of the article is to increase awareness among health and sports professionals to cooperate in the development and implementation of efficient measures in order to improve physical activity of the population. Methods: This systematic literature review focuses on the factors influencing physical activity and health-related quality of life. It also pinpoints the measures to increase the physical activity. The review article includes researches indexed in the Web of Science-SCI-EXPANDED and SSCI databases published in the English language between the years of 2000 and 2010. Results include 46 sources while the theoretic framework cites an additional 43 sources. Results: An individual's decision to be active is influenced by personal traits and by broader social and economic environment. The determining factors are age, gender and health status. Individual population groups are additionally influenced by different specific factors. Efficient measures to promote physical activity are based on the identified factors and should be directed towards those groups. Discussion and conclusion: The variety of population groups and influencing factors serves as the basis to plan preventive action and interventions. Health, sports and related organizations should work hand-in-hand to develop targeted programs and take advantage of the existing legal framework.
Keywords: health; kvaliteta življenja; leisure time; policy measures; prosti čas; quality of life; recreation; rekreacija; Slovenia; Slovenija; sport; šport; ukrepi; zdravje